MPEG Surround - Quackenbush, Schuyler R.; Herre, Jürgen (IEEE Multimedia Magazine, 2005)
MPEG's most recent effort to progress the state of the art is the MPEG Surround work item. It provides an efficient method for coding multichannel sound via the transmission of a compressed stereophonic (or even monophonic) audio program plus a low-rate side-information channel. Benefits of this approach include backward compatibility with pervasive stereo playback systems while permitting next-generation players to reconstruct high-quality multichannel sound. © 2005 IEEE.
herre_books_journals